Proceedings of Corfu Summer Institute 2021 "School and Workshops on Elementary Particle Physics and Gravity" — PoS(CORFU2021) 2022
DOI: 10.22323/1.406.0359
|View full text |Cite
|
Sign up to set email alerts
|

Geodesics, complexity and holography in (A)dS_2

Abstract: We consider spacelike geodesics in two-dimensional spacetimes. In the case of the AdS 2 black hole, their length increases linearly with time for long times, compared to the inverse temperature. In dS 2 , spacelike geodesics anchored at the same time, only exist at t = 0. To interpret this result holographically, we embed a patch of dS 2 inside an AdS 2 spacetime. In that case, geodesics only exist for a time of order the inverse temperature and their length decreases with time. We comment on possible implicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Notably, we see that all these symmetric geodesics have the same geodesic length, in other words the length is independent of E. As also pointed out in [39,40], even in the limit E → ∞, the geodesic length remains πℓ. This could be considered surprising as one typically expects spacelike geodesics to become null in this limit.…”
Section: Jcap05(2024)118supporting
confidence: 67%
See 2 more Smart Citations
“…Notably, we see that all these symmetric geodesics have the same geodesic length, in other words the length is independent of E. As also pointed out in [39,40], even in the limit E → ∞, the geodesic length remains πℓ. This could be considered surprising as one typically expects spacelike geodesics to become null in this limit.…”
Section: Jcap05(2024)118supporting
confidence: 67%
“…When the conserved quantity E approaches infinity, the spacelike geodesics from the north pole at τ N = 0 get ever closer to future infinity before they turn around and reach the south pole at τ S = 0. For any other (symmetric) time, no (real) spacelike geodesics exist that connect two conjugate points [40,46]. As our analysis of the SdS causal structure has shown, introducing a black hole in de Sitter significantly affects the above situation for a pair of conjugate static sphere observers.…”
Section: Spacelike Geodesics Between Static Sphere Observers In Sdsmentioning
confidence: 87%
See 1 more Smart Citation
“…There, it was also suggested that the double scaled Sachdev-Ye-Kitaev model [138] might have this feature. Several works have tried to make this relation more precise [139][140][141][142][143][144][145][146][147]; however, at the time of writing, the status of chaos and complexity in dS remains inconclusive [48,[148][149][150][151][152][153][154][155].…”
Section: Pos(modave2022)003mentioning
confidence: 99%
“…Based on the worldline formalism of quantum field theory, in the large mass limit one might expect that the correlator (36) is obtained by computing the length of a spacelike geodesic connecting the two points. However, there are no real, finite-length geodesics between the two points at T > 0 [67,68]. Instead, the oscillatory form of the correlator in the large mass limit ∆ ∆ ≫ 1-see the second line in equations ( 32) and ( 35)-suggests the existence of complex geodesics that might account for this two-point function.…”
Section: Spacelike Separationmentioning
confidence: 99%